Design for the Third Place Based on Satisfaction of Public’s Demand- A Case Study of Taipei Main Station District - Li , Chia-Nung; Hsiesh , Yi-Kai; Wei , Tzu-Han (International Journal of Membrane Science and Technology, 2023)
This study aims to investigate the demand for third spaces in micro-cities and explore people's perception, desire to stay, and willingness to revisit these spaces through questionnaire surveys and SEM structural model analysis. In micro-cities, integrating the "micro-mobility" mode such as walking or cycling for short-distance travel, we can create small squares, public green spaces, and pocket parks around micro-spaces to enrich the street space and enhance community belonging and identity. These micro-spaces not only serve as development areas for the functions of third spaces in micro-cities but also act as permeable boundaries within the city, achieving balanced planning and utilization. The research findings indicate that people have relatively weak awareness of third spaces but are generally satisfied with the existing planned spaces and believe that third spaces can enrich the urban environment. Dynamic urban spaces have a strong appeal to people, and the experiences and services provided by these spaces can attract people to visit. Therefore, designing spaces that stimulate interaction and communication is crucial. Additionally, the aesthetic quality of the spaces also has a certain influence on people's willingness to revisit them